Experimental study regarding the cavitation and corrosion resistance of Stellite 6 and self-fluxing remelted coatings - Ciubotariu, Costel-Relu (Strojniški vestnik, 2016)
This paper aims to compare cobalt-based (type Stellite 6) and nickel-based self-fluxing alloys (type NiCrBSiMo) regarding both their cavitation erosion resistance and corrosion resistance. The two types of protective layers were thermally sprayed onto a substrate of martensitic stainless steel. In order to improve the layers% characteristics and their metallurgical bonding to the substrate, the Stellite 6 coating was laser remelted, while the NiCrBSiMo coating was treated by flame fusion. The cavitation erosion resistance of the two materials was evaluated by measurements of the mean depth of erosion developed during a testing period of 165 minutes, using a 20 kHz ultrasonic vibrator at a peak-to-peak amplitude of 50 %m. In addition, the corrosion resistance of the layers was assessed by potentiodynamic corrosion tests carried out in H 2 SO 4 + NaCl solution at room temperature, using calomel as reference electrode. In order to highlight the differences regarding the behaviour of the two protective materials, the authors also carried out microstructural investigations of the layers before and after exposure to cavitation and corrosion. The investigations showed that both types of layers can provide improved protection of the martensitic stainless steel substrate against cavitation, whilst the NiCrBSiMo coating additionally confers significantly increased resistance to corrosion.
Keywords: hidravlični stroji; korozijska odpornost; lasersko pretaljevanje; plamenska obdelava; samotaljive zlitine; Stellite 6; toplotno nabrizgavanje